The importance of civic education in elementary school: raising awareness among students about the relevance of voting and its impact on society (Research, Society and Development, 2024)
The text emphasizes the importance of Civic Education in Elementary School to educate young people about their rights and responsibilities as citizens. It addresses the research conducted in extension projects, aiming to discuss the relevance of voting and political awareness among young voters through debates and lectures. It highlights the need to combat the increase in null and blank votes, encouraging active participation of young people in democratic life. The theoretical framework emphasizes the evolution of voting rights in Brazil and its significance as a tool for social change. Interdisciplinarity in basic education is highlighted as a way to promote a critical and responsible formation of citizens from an early age, preparing them for an active role in building a democratic future. In summary, Civic Education goes beyond teaching voting; it also promotes values such as respect, tolerance, and civic responsibility, contributing to a fairer, more participatory society committed to collective well-being.